Accumulation of Absorbed Fly Ash Particulate Matter and its Impact on the CC Process. (January 2016) - Schallert, B.; Dux, D.; Neuhaus, S.; Satterley, C.J.
Abstract: Fly ash entering a CO2 capture plant in the incoming coal-fired flue gas is a potential source of metals which support as catalysts the formation of degradation products in the MEA solvent. This study presents an assessment of the accumulation of absorbed particulate matter and an evaluation of the impact on the CC process. The particulate matter which is absorbed inside the CC plant and the ratio of flue gas flow to the installed liquid inventory determine the rate of accumulation. Filtration or settlement of particulate matter inside the process does not avoid leaching. The results of one ash sample from an European power station are presented leached with fresh 30 wt% lean MEA at different ratios (1:10 to 1:2000g/g, ash/solvent) The results show that mobility of the trace elements Cu, V, Mn increases significantly to lower ash concentrations compared to the Fe mobility values. Dissolved Fe concentrations of 0.5-1.0mg/L derive from leached fly ash after approximately 500hours of operation provided that 1mg/m 3 is absorbed and a high ratio of flue gas flow to liquid inventory is installed. Small dissolved Fe concentrations might still trigger the formation of degradation products.